2009
DOI: 10.1186/1477-7819-7-33
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous colorectal adenocarcinoma and gastrointestinal stromal tumor in Meckel's diverticulum; an unusual association

Abstract: Background: Coexistence of gastrointestinal stromal tumor with synchronous or metachronous colorectal cancer represents a phenomenon with increasing number of relative reports in the last 5 years. Synchronous occurence of GISTs with other gastrointestinal tumors of different histogenesis presents a special interest. We herein report a case of GIST in Meckel's diverticulum synchronous with colorectal adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 19 publications
0
5
0
2
Order By: Relevance
“…Benign (leiomyomas, angiomas, lipomas) and malignant (adenocarcinoma, sarcoma, carcinoid tumour and (Gastrointestinal stromal tumor) neoplasms are known [4,6,7]. No malignant histology was identified in our patient.…”
Section: Discussionmentioning
confidence: 68%
“…Benign (leiomyomas, angiomas, lipomas) and malignant (adenocarcinoma, sarcoma, carcinoid tumour and (Gastrointestinal stromal tumor) neoplasms are known [4,6,7]. No malignant histology was identified in our patient.…”
Section: Discussionmentioning
confidence: 68%
“…A review of case reports in the literature showed that stromal tumours of the small intestine are mostly small and are associated with low to intermediate risk when classified according to Fletcher's risk classification [17]. (Tables 1 and 2) [4,10,12,13,[18][19][20][21][22][23]. The presented case also had a small ileum-originated low-risk GIST.…”
Section: Discussionmentioning
confidence: 99%
“…12 The role of this thorough search has clearly not been made obsolete by the tremendous advances in preoperative imaging modalities and hence its importance cannot be understated. The impact of synchronously existing tumours on the overall prognosis of a patient must be considered when planning therapy in such instances as well.…”
Section: Discussionmentioning
confidence: 99%